A Balance Between Capture and Release: How Nanochaperones Regulate Refolding of Thermally Denatured Proteins. Issue 19 (30th March 2021) - Ma, Feihe; Wu, Xiaohui; Li, Ang; Xu, Linlin; An, Yingli; Shi, Linqi
Abstract: Nanochaperones have been designed and used for regulating the (re)folding of proteins, treating protein misfolding‐related diseases, and, more recently, in drug delivery. Despite various successes, a complete understanding of the working mechanisms remains elusive, which represents a challenge for the realization of their full potential. Here, we thoroughly investigated the functioning of differently charged nanochaperones that regulate the refolding of thermally denatured lysozyme. We found that the balance between the capture and release of lysozyme clients that are controlled by nanochaperones plays a key role in regulating refolding. More importantly, the findings could be applied to other enzymes with various physicochemical properties. On the basis of these results, we could recover the activity of enzymes with high efficiency either after 20 days of storage at 40 °C or heating at high temperatures for 30–60 min. Our results provide important new design strategies for nanochaperone systems to improve their properties and expand their applications. Abstract : The two working mechanisms of nanochaperones in regulating the refolding of thermally denatured lysozyme were fully deciphered. The balance between the capture and release of client proteins that are controlled by nanochaperones plays a key role in regulating the refolding of denatured proteins, regardless of the ATP‐independent or ATP‐dependent chaperones.